Konsentrasi Basic Fibroblast Growth Factor (bFGF) dan Transforming Growth Factor-Beta 1 (TGF-β1) pada Penyembuhan Luka Kulit Tikus - Anggi Puspa Nur Hidayati; Wira Alwysaputro; Afif Ramdisa; Restu Syamsul Hadi (Politeknik Negeri Jember, 2023)
Acceleration of wound healing is now becomes a trend center for many researcher to explore various herbs which are containing compounds that can affecting some factors involved in wound healing process. Growth factors is one of the marker that can be analyzed whether a certain herb can accelerate wound healing. To better understand how a certain herb invloved in the acceleration of wound healing, a growth factors-study was conducted. Archived skin tissue of rats from previous study (unpublished) which were been treated with Anredera cordifolia (Binahong) extract were used, and subjected to enzyme-linked immunosorbent assay (ELISA) to quantify bFGF and TGF-β1. The results obtained was then analyzed descriptively between the control group (Binahong-untreated) and treatment group (Binahong-treated). The ELISA results showed no siginificant difference of bFGF and TGF-β1 concentration between control group (Binahong-untreated) and treatment group (Binahong-treated). However, the concentration of bFGF dan TGF-β1 on day 14 were decreasing compared with those concentration on day 7, assumed the wound healing phase has already entering the next phase where the production of bFGF and TGF-β1 have been replaced with other growth factors involved in wound healing process